Штучний інтелект та академічна доброчесність: знаходження балансу - Слісаренко, Р. В. (ХНУРЕ, 2024)
Artificial Intelligence in Education (AIED) is changing education, impacting everyone involved in teaching and learning. Although AIED applications have improved learning outcomes and experiences, they also raise concerns about academic integrity, particularly regarding plagiarism and learner independence. In this article, we explore the opportunities presented by AIED and the potential challenges related to academic integrity that it raises. We also suggest a collection of ethical principles to provide guidance for informing all stakeholders.
Keywords: штучний інтелект; академічна доброчесність